Isolation Treatment Room As A Form Of Separation Room For Covid-19 Patients In Surabaya Hajj General Hospital - Putra, Heristama Anugerah; Roosandriantini, Josephine (Universitas Aisyiyah Yogyakarta, 2021)
The Surabaya hajj general hospital is one of the main reference points for patients suffering from Covid-19 in East Java province. The need and the addition of isolation space is very important and urgent to limit the space and interaction while the patient is confirmed positive from the environment. Existingly, the existing inpatient rooms are used as isolation rooms. The research method used is exploring situations with descriptive design through literature analysis and user investigation combined with the privacy space method. The results of this study were to obtain the formation of space isolation patterns based on the level of privacy in order to prevent infection out of space.